Ograniczenia dostępu do informacji publicznej – zagadnienia wybrane - Dolnicki, Bogdan (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
Access to public information is one of the most important principles of modern democracy and civil society. One of the more problematic issues related to the assessment of the status of information as public is the assessment of the nature of the so-called information or internal document. As documents that will only help in taking action, they should not be qualified as public information. However, determining whether a given information is public requires an in-depth examination of the facts. Another issue discussed is „simple information and processed information” and the notion of public interest, which determines the right to publicly processed information.
Keywords: simple information; information processed; internal information; Public information